Application of Student Worksheets Based on Hyperdocs in Chemistry Learning on Scientific Creativity - Detris Poba; Taslima; Daud K. Walanda; Mery Napitupulu; Sitti Rahmawati (Jurnal Pendidikan Kimia Indonesia, 2023)
Creativity problems are now considered a crucial ability/skill for the future of education and work. Currently, creativity is seen as urgently needing to be improved in the learning process to achieve better learning quality. This research was a descriptive-qualitative that aims to describe the utilization of Hyperdocs towards scientific creativity of SMA Labschool UNTAD Palu students in chemistry learning on the buffer topics The research subjects consisted of 20 students who were obtained based on a purposive sampling technique. The data collection instrument used hyperdocs-based worksheets which consisted of 14 scientific creativity questions that had been validated by a team of experts. Based on the analysis of percentage data and the category of scientific creativity, the test questions in the first and second sessions showed that the average scores for the aspects of unusual uses, problem finding, product improvement, creative imagination, and problem-solving were in a good category. Furthermore, the science experiment and product design aspects are in the sufficient category. So that it can be said that overall the scientific creativity of SMA Labschool UNTAD Palu class XI MIA 1 is in a good category.